Toward Development of Neuron Specific Transduction After Systemic Delivery of Viral Vectors - Finneran, Dylan J.; Njoku, Ikenna P.; Flores-Pazarin, Diego; Ranabothu, Meghana R.; Nash, Kevin R.; Morgan, David; Gordon, Marcia N. (Frontiers in Neurology, 2021)
Widespread transduction of the CNS with a single, non-invasive systemic injection of adeno-associated virus is now possible due to the creation of blood-brain barrier-permeable capsids. However, as these capsids are mutants of AAV9, they do not have specific neuronal tropism. Therefore, it is necessary to use genetic tools to restrict expression of the transgene to neuronal tissues. Here we compare the strength and specificity of two neuron-specific promoters, human synapsin 1 and mouse calmodulin/calcium dependent kinase II, to the ubiquitous CAG promoter. Administration of a high titer of virus is necessary for widespread CNS transduction. We observed the neuron-specific promoters drive comparable overall expression in the brain to the CAG promoter. Furthermore, the neuron-specific promoters confer significantly less transgene expression in peripheral tissues compared with the CAG promoter. Future experiments will utilize these delivery platforms to over-express the Alzheimer-associated pathological proteins amyloid-beta and tau to create mouse models without transgenesis.